Prevalence of colonizing bacteria and their association with primary bacteremias in hemodialysis of a university hospital - Quiñonez Olivas, Carlos; Rivera Morales, Irma; Sánchez Martínez, Concepción; Ibarra Sifuentes, Héctor Raúl; Flores Pérez, Rómulo Omar; Cárdenas de la Garza, J. A. (UANL. Facultad de Medicina, 2014)
to be from 2.5 to 5.5 cases per 1,000 catheter-day. the clinical impact is relevant and increases the cost of the HD Unit. Methods: The present study is the irst of 2 phases. It was conducted from January to December of 2012, and included all patients and nurses who were in the HD Unit. The prevalence of Gramnegative bacilli (GNB) and methicillin-resistant Staphylococcus aureus (MrSA) colonizing the nasal passages and the skin is described. Also, phenotypic association was sought by genus, species and sensitivities between colonizing bacterial strains and blood cultures with GNB and MRSA. Results: the study included 70 patients and 10 nurses. the prevalence of nasal colonization in patients by GNB was 9% and 6% in the pericatheter, and no nursing GNB colonization was discovered. The prevalence of MRSA nasal colonization was 19% and 6% in the pericatheter for patients and in the nurses the nasal colonization was 50% and 10% in the hands. We identiied 29 cases of primary bacteremia. The primary bacteremia rate is 1.5 per 1,000 catheter-day or 0.4 episodes per patient per year. Conclusion: We demonstrated a high prevalence of MrSA colonization in patients and nurses in the HD Unit. No relationship was found between primary bacteremia by GNB and patients and nurses’ bacteria colonization by the phenotypic comparison.